Binding of Benzanthrone Dye ABM to Insulin Amyloid Fibrils: Molecular Docking and Molecular Dynamics Simulation Studies - Vus, Kateryna (East European Journal of Physics, 2020)
The binding of the benzanthrone dye ABM to the model amyloid fibrils of human insulin, referred to here as vealyl (12-VEALYL-17, insulin B-chain)), lyqlen (13-LYQLEN-18, insulin A-chain) and Insf ( 11-LVEALYL-17, B-chain) + 12-SLYQLENY-19, A-chain) was studied by the molecular docking and molecular dynamics simulations. To obtain the relaxed structures with the enhanced conformational stability, the model fibril structures were solvated and equilibrated in water at 300-310 K using the Gromacs simulation package, with backbone position restraints being applied to prevent the beta-sheet disruption. It appeared that the vealyl fibril relaxation resulted in the twisting of the two β-sheets, and only the vealyl fibril remained stable during 20 ns MD simulations of the relaxed structures. Next, Insf, vealyl, lyqlen, and vealyl (relaxed) fibrils were used for the molecular docking studies (by SwissDock), revealing the binding modes of ABM and standard amyloid marker Thioflavin T (ThT) to the examined fibril structures. Specifically, in the most energetically stable complex the vealyl (relaxed) fibril binding site for ABM was located on the dry steric zipper interface, although the dye was associated with only one twisted β-sheet. During the 20 ns MD simulation the ABM fibril location was changed to a deeper position in the dry interface between the two β-sheets, with the dye-interacting residues being represented by 6 LEU, 3 VAL, 2 ALA, 1 TYR and 1 GLU. The binging free energy Δ(Gbinding) for ABM complexation with vealyl (relaxed) fibril evaluated with the GMXPBSA GROMACS tool was found to be –31.4±1.8 kJ/mol, that is in accordance with our estimates derived from the fluorescence studies for ABM binding to the bovine insulin amyloid fibrils Δ(Gbinding)= –30.2 kJ/mol. The Lennard-Jones component appeared to dominate the dye-fibril interactions, with much smaller contributions of Coulombic and nonpolar solvation terms to the total Δ(Gbinding) value, and unfavorable effect of the polar solvation term. These findings indicate that a high specificity of ABM to the insulin amyloid fibrils may arise predominantly from the dye-protein hydrophobic interactions, followed by the formation of van der Waals contacts, thus providing additional evidence for sensitivity of the dye spectral properties to environmental polarity, suggested in our previous studies. Overall, the obtained results provided further insights into the atomistic mechanism of the ABM binding to insulin amyloid fibrils and can be used for development of the novel fluorescent reporters possessing high sensitivity to the amyloid assemblies.